Factors associated with dry mouth in dependent Japanese elderly. (7th June 2012) - Kakudate, Naoki; Muramatsu, Tsukasa; Endoh, Mami; Satomura, Kazuhito; Koseki, Takeyoshi; Sato, Yuji; Ito, Kayoko; Ogasawara, Tadashi; Nakamura, Seiji; Kishimoto, Etsuo; Kashiwazaki, Haruhiko; Yamashita, Yoshihisa; et al.
<x xml:space="preserve">Abstract</x> Objectives To identify factors associated with dry mouth. Background Dry mouth adversely affects oropharyngeal health, particularly in elderly, and can lead to pneumonia. A better understanding of the epidemiology of dry mouth is therefore important in improving treatment strategies and oral health in high‐risk elderly patients. Methods We conducted a cross‐sectional study involving 383 dependent Japanese elderly individuals (65–84 [n = 167] and ≥85 [n = 216] years) at eight long‐term care facilities and hospitals. Thirty‐four potential factors associated with dry mouth were examined by multiple logistic regression analysis. The primary outcome was dry mouth, as diagnosed by tongue dorsum moisture. Results We identified that body mass index and severity of physical disability were identified as a potential factors associated with dry mouth in the super‐elderly (≥85 years) group, whereas severity of physical disability, outcome measurement time, high daily water consumption, mouth breathing, use of antidepressants and diuretics, and high frequency of daily brushing (≥2 times per day; Odds ratio: 5.56; 95% Confidence Interval: 1.52–20.00) were associated with dry mouth in the 65‐ to 84‐year‐old group. Conclusion To our knowledge, this is the first study to identify a link between frequency of daily brushing and dry mouth and suggests that tooth brushing should be encouraged in high‐risk dependent Japanese elderly (65–84 years), particularly those taking antidepressants and/or diuretics.